Pengembangan bahan ajar interaktif canva (BAIC) berbasis deep learning untuk meningkatkan berpikir kritis siswa pada materi luas bangun datar - wahyu dwi herawati; Zainnur Wijayanto (Jurnal Pendidikan Dasar, 2025)
This research aims to develop Bahan Ajar Interaktif Canva (BAIC) based on deep learning and test its effectiveness in improving elementary school students' critical thinking skills on the material of flat shape area. This study uses the Research and Development (R&D) method of the ADDIE model consisting of the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were grade IV elementary school students who were selected purposively. Data collection instruments included expert validation sheets, teacher and student response questionnaires, and critical thinking tests. The results of expert validation showed that BAIC was in the very valid category (average validation score> 86%). The conclusion of this study is that deep learning-based BAIC is worthy of being used as an alternative interactive teaching material that supports critical thinking-based mathematics learning.